“Control químico de malezas en el cultivo de Sorgo (Sorghum spp.) y su incidencia en la producción” - Suárez Conforme, Sergio Jacinto (2022)
This document refers to the chemical control of weeds in the cultivation of Sorghum (Sorghum spp.) and its impact on production. The integrated management of weeds in sorghum should consider the application of timely control practices to avoid direct damage due to weed competition for light, water and nutrients. Among the conclusions, it was determined that in Ecuador, the potential areas where sorghum adapts very well are in the provinces of Guayas, Manabí, El Oro and Los Ríos. It can also be cultivated in soils that remain fallow after the rainy season, in which rice had previously been planted as the main crop; chemical weed control is the main method of weed control in sorghum cultivation, through the correct application of herbicides and efficient and timely application of these products; the main weeds present in sorghum are straw, mucus of turkey (Echinochloa spp.) treadmill (Rottboelliia spp.) chicken leg (Eleusine indica) straw mona (Leptochloa filiformis) dew guard (Digitaria sanguinalis) Johnson grass (Sorghum halapense) false treadmill (Schaemun rugosum) Bledos (Amaranthus spp.) Purslane (Portulaca oleracea) and the herbicide combinations that provided the best percentage of weed control is Atrazine + Pendimethalin.